1975
DOI: 10.1021/je60066a027
|View full text |Cite
|
Sign up to set email alerts
|

Heats of dilution of aqueous electrolytes. Temperature dependence

Abstract: The heats of dilution of KCI, MgCI2, Na2S04, and MgS04 were measured over a concentration range of 0.005-2.Om at temperatures between 40-80°C. The data were extrapolated to infinite dilution by use of the Debye-Hückel limiting law to obtain relative apparent molal heat contents ( _). The heats of dilution of MgCI2 and MgS04 were measured at 25 °C and combined with the low concentration work of Lange and Streeck to yield values of L. The relative partial molal heat content of solvent and solute was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(43 citation statements)
references
References 5 publications
4
39
0
Order By: Relevance
“…Both results, ours and the reference, are in good agreement over the whole range of concentration •, results by Snipes et al (4) considered in this work. The experimental osmotic coefficients of magnesium chloride were fitted by the Hamer and Wu (5) equation:…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Both results, ours and the reference, are in good agreement over the whole range of concentration •, results by Snipes et al (4) considered in this work. The experimental osmotic coefficients of magnesium chloride were fitted by the Hamer and Wu (5) equation:…”
Section: Resultssupporting
confidence: 90%
“…In figure 1, the experimental osmotic coefficients of magnesium chloride, obtained in this study, together with those reported by Snipes et al (4) are shown for comparison. Both results, ours and the reference, are in good agreement over the whole range of concentration •, results by Snipes et al (4) considered in this work.…”
Section: Resultsmentioning
confidence: 64%
“…Dilution enthalpies have been reported close to room temperature by Wallace and Robinson, (10) Thompson et al, (11) Leung and Millero, (12) and to T = 472.95 K by Mayrath and Wood. (13) Snipes et al (14) reported apparent relative molar enthalpies at the intermediate temperatures 313.15 K, 335.25 K, and 355.15 K, but their values were obtained by fitting experimental results of the enthalpy of dilution.…”
Section: -9614/02mentioning
confidence: 99%
“…[10]) were regressed from the temperature-dependent correlation given by Greenberg & Moller (1989) for 0-250û C and I ≤ 18 m. The correlations of Greenberg & Moller (1989) were assessed by comparing predictions with the following activity/osmotic coefficient data for the KCl-H 2 O system: Robinson & Stokes (1959) and Hamer & Wu (1972) at 25û C, Harned & Owen (1958, pg. 727) at 0-40û C, Hellams et al (1965) at 45û C, Humphries et al (1968) at 60û C, Moore et al (1972) and the data of Snipes et al (1975; as given by Zemaitis et al, 1986, pg. 138) at 80û C, and Holmes et al (1978) at 109û C. There was good agreement.…”
Section: Potassium Chloride (Kcl)mentioning
confidence: 96%